2017
DOI: 10.1186/s12944-017-0471-0
|View full text |Cite
|
Sign up to set email alerts
|

PPBP and DEFA1/DEFA3 genes in hyperlipidaemia as feasible synergistic inflammatory biomarkers for coronary heart disease

Abstract: BackgroundCoronary heart disease (CHD) is an important complication of atherosclerosis. Biomarkers, which associate with CHD development, are potential to predict CHD risk. To determine whether genes showing altered expression in hyperlipidaemia (H) and coronary heart disease (CHD) patients compared with controls could be CHD risk biomarkers.MethodsControl, H, and CHD groups represented atherosclerosis to CHD development. Gene profiling was investigated in peripheral blood mononuclear cells using DNA microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 66 publications
3
24
0
Order By: Relevance
“…Among these proteins, some of them have been reported clinically, such as Fatty acid binding protein3 (FABP3) (8-10), Pro-platelet basic protein (PPBP) (11), and C4B (12)(13)(14)(15). Our study validates these results and provides further clinical evidence for the application of these proteins in clinical practice.…”
Section: Discussionsupporting
confidence: 82%
“…Among these proteins, some of them have been reported clinically, such as Fatty acid binding protein3 (FABP3) (8-10), Pro-platelet basic protein (PPBP) (11), and C4B (12)(13)(14)(15). Our study validates these results and provides further clinical evidence for the application of these proteins in clinical practice.…”
Section: Discussionsupporting
confidence: 82%
“…We identified 55 intersecting genes between FH and FH-CHD groups. Similar to our previous study (Maneerat et al, 2017), the expressions of intersecting genes that shared between FH and FH-CHD groups are potential for further development as predictive markers for FH-CHD in FH patients. In this study, we selected that 10 of 55 genes, MAPK14, TRPM2, STARD8, PDLIM5, BCL3, BLOC1S5, GBA, RBMS1, CD14, and CD36 showed significant co-expression and potentially play roles in chronic inflammation and pathways related to pathogenesis of CHD.…”
Section: Introductionsupporting
confidence: 79%
“…It can also stimulate a variety of processes, such as mitogenesis, glucose metabolism, and the synthesis of the extracellular matrix and plasminogen activator (49,50). Maneerat et al identified PPBP as one of the significant biomarkers correlated with the development of coronary heart disease (CHD) (51). CXCL12 (also known as SDF-1) belongs to the CXC family, a subclass of the chemokine family, and regulates cellular activity by binding to CXCR4 or CXCR7, which are receptor proteins located in the cytomembrane, contributing to the activation of various intracellular signaling pathways (52)(53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%